Group B streptococci in pharyngeal aspirates at birth and the early detection of neonatal sepsis. Issue 7 (July 1978) - Slack, M P; Mayon-White, R T
Abstract : The pharyngeal aspirates collected from 400 babies at the time of delivery were examined for the presence of bacteria, especially group B streptococci. Aspirates from 79 babies were found to contain viable bacteria, including 4 with group B streptococci; one of these 4 babies developed streptococcal meningitis within 24 hours. The group B streptococci were seen on a Gram-stained film of the aspirate, and were detectable by coagglutination and countercurrent immunoelectrophoresis within 4 hours and by culture after 24 hours. Examination of pharyngeal aspirates may be of value as a screening test for neonatal sepsis.